Neologizmy słowotwórcze w Obserwatorium Językowym Uniwersytetu Warszawskiego (na materiale haseł opracowanych do lutego 2022 roku). Część 1: Substantywne derywaty proste - Rybarski, Mateusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
This article constitutes the first part of paper cycle devoted to 1,117 Polish derivational neologisms in Obserwatorium Językowe Uniwersytetu Warszawskiego (Language Observatory of University of Warsaw). Its aim is to present and analyze 572 new substantival derivatives in the Polish language. The author divides them into groups of derivational neologisms created by the use of the same formative technique and affix. He states that 529 of them were formed by the use of 37 suffixes, 19 – with 8 prefixes, 16 – by the change of paradigm and 8 – by adding prefix and suffix simultaneously. The study concludes that the biggest class of described new substantival derivatives in contemporary Polish language consists of suffixal structures. As for morphemes used to create them, suffixes -ka, -(ów)ka and -(ow’)ec turned out to be the most productive.